Fiber Protein Produced in Escherichia coli as a Subunit Vaccine Candidate Against Egg-Drop Syndrome 76 - Wang, Linguo; Zhang, Pantao; Huang, Baicheng; Wang, Mengyue; Tian, Hui; Liu, Peng; Liu, Wujie; Tian, Kegong (Frontiers in Veterinary Science, 2022)
The egg-drop syndrome ‘76 (EDS ‘76) caused by duck atadenovirus A (DAdV-1) infection in laying hens leads to the decrease in egg production, causing heavy economic losses in the poultry industry; thus, vaccines with high safety and immunogenicity are needed. In this study, the DAdV-1 fiber protein expressed in Escherichia coli with codon optimization showed the hemagglutination (HA) titer of 13 log2 after purification (0.6 mg/mL). Compared with inactivated EDS ‘76 vaccine, the specific pathogen-free chickens immunized with 0.4 mL fiber protein (HA titer of 11 log2) induced an equal level of HA inhibition (HI) titer and neutralizing antibodies. Meanwhile, after immunization with fiber protein, the lowest HI titer that could provide the effect to reduce egg production rate in laying hens after the challenge was 7 log2. Moreover, fiber protein with an HA titer of 7 log2 could induce an HI titer no <7 log2 in laying hens, which was equal to or higher than the lowest HI titer (7 log2) that could reduce egg production against DAdV-1 infection significantly, indicating that it is economically feasible for vaccine development. Importantly, the HI antibodies maintained at a high level up to 180 days postimmunization contribute to the clinical application of the vaccine candidate. Overall, the fiber protein produced in E. coli is an effective subunit vaccine candidate in EDS ‘76 control for its high immunogenicity and protection in chickens.